2011
DOI: 10.1007/s00011-011-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of leflunomide on CD4+CD25+Foxp3+ T regulatory cells in mice receiving allogeneic bone marrow transplantation

Abstract: LEF decreases peripheral CD4(+)CD25(+) Treg cells in un-immunizing and immunizing recipients, indicating that LEF might not be an ideal candidate for the treatment of autoimmune diseases or graft rejection with respect to induction of immune tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Our study found that low-dose sirolimus (0.5 mg per other day with the serum concentration of 1.8 ± 0.4 ng/ml) had an immunoregulatory property besides immunosuppression by the rebalancing of Th17 and Tregs. Conventional immunosuppressant medications can alleviate disease activity by inhibiting lymphocytes nonspecifically [28, 29]. Our results showed that conventional immunosuppressive strategy not only decreased the proinflammatory Th17 cells but also reduced anti-inflammatory Tregs, which may aggravate the disturbance of the immune balance.…”
Section: Discussionmentioning
confidence: 75%
“…Our study found that low-dose sirolimus (0.5 mg per other day with the serum concentration of 1.8 ± 0.4 ng/ml) had an immunoregulatory property besides immunosuppression by the rebalancing of Th17 and Tregs. Conventional immunosuppressant medications can alleviate disease activity by inhibiting lymphocytes nonspecifically [28, 29]. Our results showed that conventional immunosuppressive strategy not only decreased the proinflammatory Th17 cells but also reduced anti-inflammatory Tregs, which may aggravate the disturbance of the immune balance.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast to the results for Th17, we observed no significant alternation in the proportions of CD4 + CD25 + Foxp3+ Tregs in LEF treated CIA mice comparing to CIA groups. In Di Jin research [ 20 ], differential changes of CD4 + CD25 + Foxp3+ Treg cells in different peripheral immune tissues or organs were observed after LEF treatment in mice with and without body mass index (BMI). The ratios of Treg cells were enhanced in the thymus, but significantly decreased in the spleens but not in PBLs and LNs.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + CD25 + Treg cells were subsequently added to each well in different ratios to CD4 + CD25 - T cells. Cells were cultured with 3μg/ml Con A at 37°C and 5% CO 2 condition for 4 days [ 12 ]. 0.5 μCi [ 3 H]thymidine (185GBq/mmol; Atomic Energy Research Establishment, China) was given for the last 16 hours.…”
Section: Methodsmentioning
confidence: 99%